Virality of evil philosophy in the time of a pandemic - Dwivedi, Divya (Rowman & Littlefield, 2022)
"The authors of this insightful and urgent collection both use the metaphor of evil as a virus or contagion and conceptualize the COVID-19 virus as a manifestation of evil to reconsider the purpose of philosophy in and for a pandemic"--